Validation study of an ex vivo porcine auricular model for simulation training in otoplasty. Issue 7 (16th July 2020) - Li, L; Okhovat, S; Milner, T; Sheikh, S
Abstract: Objective: To perform a validation assessment of a novel porcine ex vivo model for otoplasty training. Methods: A total of nine otolaryngology trainees performed a standard approach otoplasty on a porcine ear. They completed a series of tasks including posterior skin incision, anterior scoring, Mustardé suture placement and concha–mastoid suture placement. Trainees completed a post-task questionnaire assessing face validity, global content validity and task-specific content validity. Results: Trainees' median scores for the porcine model were: 4 for face validity (interquartile range, 3–4), 5 for global content validity (interquartile range, 4–5) and 4 for task-specific content validity (interquartile range, 4–4). Conclusion: This study is the first to formally validate the ex vivo porcine auricular model as a useful tool for training in otoplasty. The model should be incorporated into simulation training for otoplasty in order to improve learning, enable acquisition of specific surgical skills and improve operative outcomes.